Dívida pública: O limiar de mudanças? - Francisco Luiz C. Lopreato (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The proposal is to discuss the dynamics of public debt and propose to carry out institutional changes in order to eliminate short-term logic dominant in the Brazilian financial market. The fall in real interest rates gave way to deepen recent changes in debt structure and eliminate the remaining traces of the period of high inflation.
Keywords: E62; H63; 330; public debt; public finance; public sector